ANALISIS KETERKAITAN STANDAR KOMPETENSI LULUSAN (SKL), KOMPETENSI INTI (KI), DAN KOMPETENSI DASAR (KD) DALAM IMPLEMENTASI KURIKULUM 2013 - Ryna Rachmawati (Balai Diklat Keagamaan Bandung, 2018)
This article aims to explain and describe the steps of the SKL KI KD analysis in the hope of helping teachers to harmonize the KD demands on the curriculum with KI achievement. Using one of the KD-3 and KD 4 examples of the 7th grade junior high school science subjects, the results obtained were that KD-3 was quite harmonious based on the thinking process dimensions and the knowledge dimensions of Anderson's Taxonomy. Although the level of KD-3 can be raised to the evaluation stage (C5) with dimensions of metacognitive knowledge, KI demands for junior high school / MTs are sufficient to procedural knowledge. Whereas in KD-4 using Dyer's taxonomy is included in the realm of abstract skills but can be said to be sufficiently aligned for the achievement of KI-4 in the concrete domain. Key words: SKL KI KD Analysis, Knowledge Taxonomy, Psychomotor Taxonomy